The Lullaby Project: A Musical Intervention for Pregnant Women - Jennifer Hinesley; Sarah Cunningham; Rashel Charles; Kirsten Olsen; Saba Masho; Susan Kornstein (Women's Health Reports, 2020)
Background: This pilot study investigated the impact of a musical intervention on maternal/fetal attachment, psychiatric symptoms, and perceived stress in two centers. Materials and Methods: Forty-four pregnant women participated from the Virginia Commonwealth University in Richmond, VA, and Jacobi Medical Center in Bronx, NY. Participants were assigned to a lullaby intervention or control group. The Maternal Fetal Attachment Scale, Perceived Stress Scale (PSS), and Symptom Checklist (SCL-27) were completed at baseline and follow-up. Results: Although no significant differences were found in maternal/fetal attachment between control and intervention groups, there were within-group differences in both groups from baseline to follow-up. No statistically significant differences in change from baseline occurred on the SCL-27 and PSS. Conclusions: Exposure to a lullaby intervention was not statistically associated with maternal/fetal attachment, mental health, and perceived stress in this pilot study. Future studies with larger samples and different outcomes are suggested.